Adversarial principle under the new civil procedure in Ukraine - Kroytor, V. A; Кройтор, В. А.; ORCID: http://orcid.org/0000-0002-1849-5721; Mamnitskyi, V.; ORCID: http://orcid.org/0000-0001-7170-7802 (Access to justice in Eastern Europe. – 2019. – № 4 (5). – P. 30-41, 2019)
Дана робота присвячена еволюції принципу змагальності в цивільному процесі в умовах постсоціалістичного регресу та пореформеного цивільного судочинства, а також запровадженню принципів ведення справ та співпраці між судом і сторонами процесу.

This work deals with the evolution of adversarial principle in civil process under the conditions of post-socialist regression and post-reform civil justice as well as the introduction of the principles of case management and cooperation between the court and the parties in the process. In particular, it analyses the main provisions of such new guarantees of realization of the right to a fair trial, which were introduced in the CPC of Ukraine in 2017-2018 as a court’s right to prevent abuse of procedural rights, as well as the exchange of competitive documents between the parties. The authors argue that effective protection of the rights today is to be based on the adversarial principles that shall be supplemented by the security of the balance of rights of the parties and the authority of the court on the examination of civil matters.

В данной работе рассматривается эволюция принципа состязательности в гражданском процессе в условиях постсоциалистического регресса и пореформенного гражданского судопроизводства, а также внедрение принципов делопроизводства и сотрудничества между судом и сторонами в процессе.
Kroitor, V. Adversarial principle under the new civil procedure in Ukraine / Volodymyr Kroitor, Valeriy Mamnitskyi // Access to justice in Eastern Europe. – 2019. – № 4 (5). – P. 30-41. – DOI: https://doi.org/10.33327/AJEE-18-2.4-a000021.
Keywords: Цивільне право. Civil Law. Гражданское право; Наукові публікації. Scientific publications. Научные публикации; publikatsii u WoS; publikatsii u zarubizhnomu vydanni; Цивільно-процесуальне право. Civil and Procedure Law. Гражданское процессуальное право; adversariality; equality of parties; principles of the civil procedure; competitiveness; procedural activity of the court; principle of cooperation between the parties and the judge; змагальність; рівність сторін; принципи цивільного процесу; конкурентоспроможність; процесуальна діяльність суду; принцип співпраці сторін і судді; состязательность; равенство сторон; принципы гражданского процесса; конкурентоспособность; процессуальная деятельность суда; принцип сотрудничества сторон и судьи